USP22 promotes hypoxia-induced hepatocellular carcinoma stemness by a HIF1α/USP22 positive feedback loop upon TP53 inactivation. Issue 7 (27th November 2019) - Ling, Sunbin; Shan, Qiaonan; Zhan, Qifan; Ye, Qianwei; Liu, Peng; Xu, Shengjun; He, Xin; Ma, Jian; Xiang, Jiajia; Jiang, Guangjiang; Wen, Xue; Feng, Zijie; et al.
Abstract : Objective: We aimed to elucidate the mutual regulation mechanism of ubiquitin-specific protease 22 (USP22) and hypoxia inducible factor-1α (HIF1α), and the mechanism they promote the stemness of hepatocellular carcinoma (HCC) cells under hypoxic conditions. Design: Cell counting, migration, self-renewal ability, chemoresistance and expression of stemness genes were established to detect the stemness of HCC cells. Immunoprecipitation, ubiquitination assay and chromatin immunoprecipitation assay were used to elucidate the mutual regulation mechanism of USP22 and HIF1α. HCC patient samples and The Cancer Genome Atlas data were used to demonstrate the clinical significance. In vivo USP22-targeting experiment was performed in mice bearing HCC. Results: USP22 promotes hypoxia-induced HCC stemness and glycolysis by deubiquitinating and stabilising HIF1α. As direct target genes of HIF1α, USP22 and TP53 can be transcriptionally upregulated by HIF1α under hypoxic conditions. In TP53 wild-type HCC cells, HIF1α induced TP53-mediated inhibition of HIF1α-induced USP22 upregulation. In TP53-mutant HCC cells, USP22 and HIF1α formed a positive feedback loop and promote the stemness of HCC. HCC patients with a loss-of-function mutation at TP53 and high USP22 and/or HIF1α expression tend to have a worse prognosis. The USP22-targeting lipopolyplexes caused high tumour inhibition and high sorafenib sensitivity in mice bearing HCC. Conclusion: USP22 promotes hypoxia-induced HCC stemness by a HIF1α/USP22 positive feedback loop on TP53 inactivation. USP22 is a promising target for the HCC therapy.